A Secure Geographic Routing Wormhole Detection for Supporting Mobile Sinks in Wireless Sensor Networks - SABRI, Yassine; Kamoun, Najib El (International Journal of Computer Sciences and Engineering, 2025)
A wormhole attack is particularly harmful against routing in sensor networks where an attacker receives packets at one location in the network, tunnels and then replays them at another remote location in the network. A wormhole attack can be easily launched by an attacker without compromising any sensor nodes. Since most of the routing protocols do not have mechanisms to defend the network against wormhole attacks, the route request can be tunneled to the target area by the attacker through wormholes. We use one of the basic routing protocols called GRPW-Mus used for Supporting Mobile Sinks in Wireless Sensor Networks . GRPW-MuS, a geographical routing protocol for wireless sensor networks , is based on an architecture partitioned by logical levels, on the other hand based on a multipoint relaying flooding technique to reduce the number of topology broadcast. GRPW-MuS uses periodic HELLO packets to neighbor detection. As introduced in Reference [9, 17], the wormhole attack can form a serious threat in wireless sensor networks, especially against many wireless sensor networks routing protocols and location-based wireless security systems. Here, a trust model to handle this attack in GRPW-MuS is provided called GRPW-MuS-s . Using OMNET++ simulation and the MiXiM framework, results show that GRPW-MuS-s protocol only has very small false positives for wormhole detection during the neighbor discovery process (less than GRPW-MuS). The average energy usage at each node for GRPW-MuS-s protocol during the neighbor discovery and route discovery is very low than GRPW-MuS, which is much lower than the available energy at each node. The cost analysis shows that GRPW-MuS-s protocol only needs small memory usage at each node, which is suitable for the sensor network.